Adhesion and corrosion resistance of polycaprolactone coating on NiTi alloy surface after alkali heat pretreatment. Issue 4 (19th October 2022) - Zhang, Zhihui; Yang, Yanan; Guo, Yunting; Sha, Pengwei; Xu, Zezhou; Yu, Zhenglei; Si, Jiashun; Zhang, Zhengao; Guo, Jia; Chen, Yifan
Abstract: Selective laser melting of nickel‐titanium alloy (SLM‐NiTi) can precisely control the size of the sample molding structure and has attracted extensive attention due to its special superelasticity and shape memory effect. However, the biological inertness and poor corrosion resistance of SLM‐NiTi alloy limit their wide application as biomedical implant materials. In this study, polycaprolactone (PCL) coating was prepared on SLM‐NiTi alloy by dipping and pulling method, and the effects of alkali heat pretreatment on the morphology, adhesion, corrosion resistance, long‐term stability and biomineralisation of the PCL coatings were investigated. The results showed that PCL coating can substantially improve the performance of SLM‐NiTi alloy, and the PCL coating after alkali heat pretreatment has higher adhesion (increased from 1, 747 to 2, 498 mN) and lower corrosion current density (reduced by about an order of magnitude compared to PCL coating alone). In addition, the necessary stability, biomineralisation and biocompatibility ability of coatings were also further improved. Therefore, the alkali heat pretreated PCL‐coated SLM‐NiTi alloy has good application prospects in implants due to its superior properties.